Computers : the user perspective - Stallings, Warren D.; Hutchinson, Sarah E.; Sawyer, Stacey C. (St.Louis : Times Mirror/Mosby College Publishing, 1988)
This book is oriented toward future computer users, not future computer specialists.
Part One. the Beginning: Becoming a Computer User -- Part Two. Hardware -- Part Three. Software -- Part Four. Systems Concepts and Applications -- Part Five. Trends -- Part Six. Microcomputers Software.
Includes bibliographical references and index.
Keywords: MICROCOMPUTERS